Talent development environments in elite taekwondo population: a study within an Italian context - Apollaro, G.; Pantanella, L.; Esposito, M.; Ruscello, B. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to analyze the quality perception of the main talent development environments within the elite taekwondo population, through the Talent Development Environment Questionnaire (TDEQ-5). METHODS: The TDEQ-5 was given to 107 top level athletes from the Italian National Team and from 12 domestic clubs. An exploratory factor analysis (EFA) was carried out and the descriptive statistics were measured for all the individual item scores; for each factor the independent t-tests were carried out to identify differences in scores between the National and the Club environments. RESULTS: The EFA revealed four principal components (56.68%). These four factors reported good reliability values (a= from 0.63 to 0.93) and significant correlations. The development environments were positively perceived by the athletes, with factor 1 being the highest performing component and factor 2 the weakest. Factor 1 was identified as the strength of the Club environment, while factor 2 as the area of improvement for the National environment. The scale values of factors 1, 2 and 3 were significantly higher (P<0.01) in the Club environment. The item-by-item analysis revealed the presence of three strengths and six areas of improvement in the national environment, eleven strengths and no areas of improvement in the Club environment. CONCLUSIONS: Our study highlights the strengths and weaknesses of the different development environments surveyed and may allow to plan targeted interventions to increase the perception of quality of the talent development environments, thus allowing the stakeholders to optimize their work.